2005
DOI: 10.1007/s10669-005-4279-5
|View full text |Cite
|
Sign up to set email alerts
|

Effect of 450 MHz Microwave Modulated with 217 Hz on Human EEG in Rest

Abstract: This study focuses on discrimination of changes, produced by low-level microwave exposure in intensity and time variability of the human EEG at rest. The power spectral density (PSD) method and nonlinear scaling analysis of the length distribution of low variability periods (LDLVP) were selected for analysis of the EEG signal. During the study, 19 healthy volunteers were exposed to a microwave (450 MHz) of 217 Hz frequency on-off modulation. The field power density at the scalp was 0.16 mW/cm 2 . The experimen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2006
2006
2010
2010

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 17 publications
1
14
1
Order By: Relevance
“…This result is in agreement with the findings reported recently, that the GSM mobile phone radiation increased the EEG power mainly in the alpha frequency band [Huber et al, 2002;Curcio et al, 2005]. Our previous results suggested that the 450 MHz microwave modulated at 217 Hz increased the EEG energy and the effect was stronger on the EEG beta rhythm in parietal and temporal regions [Bachmann et al, 2005b]. It is interesting to note that the effect caused by a chemical stressor results in similar changes in the resting EEG; an increased beta absolute power has also been observed in alcohol-dependent subjects [Rangaswamy et al, 2002].…”
Section: Discussionsupporting
confidence: 94%
“…This result is in agreement with the findings reported recently, that the GSM mobile phone radiation increased the EEG power mainly in the alpha frequency band [Huber et al, 2002;Curcio et al, 2005]. Our previous results suggested that the 450 MHz microwave modulated at 217 Hz increased the EEG energy and the effect was stronger on the EEG beta rhythm in parietal and temporal regions [Bachmann et al, 2005b]. It is interesting to note that the effect caused by a chemical stressor results in similar changes in the resting EEG; an increased beta absolute power has also been observed in alcohol-dependent subjects [Rangaswamy et al, 2002].…”
Section: Discussionsupporting
confidence: 94%
“…This is somewhat different from what has been observed for the modulation frequency 7 Hz, when the sign of the departure was always negative (corresponding to increased variability) (Bachmann et al 2005a). However, the outcome of a study at modulation frequency 217 Hz, in which for half of the subjects the computed LDLVP weighted area decreased and for another half it decreased (Bachmann et al 2005b), coincides with current results at 40 Hz. The S-parameter measures exceeded the limit of significant deviation from zero hypothesis also at modulation frequency 40 Hz in beta2 frequency band (Table 1), providing two significant cases out of 15, that is 13.3%.…”
Section: Discussioncontrasting
confidence: 92%
“…The results reported in our previous study with 7 Hz modulated microwave lead to the conclusion that the effect appears in time variability (Bachmann et al 2005a), while the next study concerning modulation frequency 217 Hz concluded that the effect is rather in intensity (Bachmann et al 2005b).…”
Section: Discussionmentioning
confidence: 78%
“…This suggests that different modulation techniques (e.g., temporal power variation, modulation frequency) in different mobile phone systems may be a biologically relevant factor [Pedersen and Andersen, 1999;Bachmann et al, 2005;Hinrikus et al, 2007Hinrikus et al, , 2008. In addition, the majority of null findings in the literature may be due to the low power level of mobile phone radiation because most studies were designed to give local SAR values at or near the permitted limits.…”
Section: Discussionmentioning
confidence: 99%